Comparative behavior of Eurypanopeus depressus (Smith) and Eurypanopeus dissimilis (Benedict and Rathbun) (Decapoda: Brachyura: Xanthidae) - Garcés B., Humberto A. (1987)
A series of experiments and observations were made on two nominate species of mud crabs. Differences were found in desiccation resistance, salinity tolerance, temperature tolerance, dominance and coexistence, aggressiveness, feeding, and response to a new habitat. Data support the scheme of previous classification, which regards them as separate species. It is concluded that Eurypanopeus depressus and Eurypanopeus dissimilis are two closely related sympatric species isolated by behavioral factors.